Mobile health technology for gestational care: evaluation of the GestAção's app - Raimunda Magalhães da Silva; Christina César Praça Brasil; Indara Cavalcante Bezerra; Francisca Francisete de Sousa Nunes Queiroz
ABSTRACT Objective: to evaluate the GestAção application, based on the experience of pregnant women use. Method: an evaluative, applied, methodological, quantitative-qualitative study. This tool was evaluated by 13 pregnant women through questionnaires for sociodemographic profile characterization and Likert scale use to calculate Content Validity Index (CVI); and semi-structured interview, with analysis based on Semiotics. Results: the study evidenced a significant level of satisfaction of pregnant women with the application use, considering the objectives (CVI = 0.92), structure and presentation (CVI = 0.86), and relevance (CVI = 0.92). Final considerations: the GestAção application obtained an overall CVI of 0.90, evidencing it as a facilitating and supporting technology in the empowerment of pregnant women interested in obtaining knowledge about pregnancy. It has been proved to be a powerful tool to qualify good practices in nursing consultation.